Integrated Numerical Investigation on the Aerodynamics Characteristic and Vortex Development of Airfoil using Spalart-Allmaras Model - Dinaryanto, Okto; Jalaali, Bahrul; Hisyam, Muhammad; Wibowo, Teguh (Indonesian Journal of Aerospace, 2023)
In this paper, the numerical simulation successfully obtained good results in analyzing fluid flow over the airfoil. Detailed explanations of simulation steps were also presented. The flow characteristics over three airfoil models were numerically simulated in this work: NACA0021, NACA2409, NACA2409+Fowler flap. The reliable Spalart-Allmaras (S-A) turbulent model was used and validated using reported data from experimental in terms of lift and drag coefficients. In this regard, the discrepancies of less than 10% were obtained for both coefficients, respectively. The boundary layer separation, vortex development, and air separation were clearly captured. The results of symmetric airfoil showed that the vortex shedding regimes occurred at α = 8o, and the stall critical-angle was about 14o. The value was higher for the NACA2409, where the airflow exhibited a relatively more stable behavior. Moreover, it is evident that flap addition altered lift-drag characteristics. The value of the lift-to-drag ratio increased due to the increase of Cl and the reduction of Cd. The parametric study was done on the α and flap deflection angle to attain the desirable airfoil configuration. The maximum result of airfoil configuration was obtained on the NACA2409 at α = 12o with 100 flap deflection angle while it enhanced the lift coefficient by about 54%. This result strengthens the robustness of the S-A turbulence model and projects the use of the S-A model for dealing with the aerodynamics analysis. This study is beneficial for initial aircraft design on the aerodynamics aspect of a wing.